Analysis of the impact of atmospheric rivers and marine heatwaves on heavy rainfall in northeastern China during the summer of 2024 - Zhang, Zhongyu; Jia, Wentao; Zhang, Weimin; Zhou, Yuliang; Gao, Zhenli (Frontiers in Earth Science, 2025)
From 18 to 21 August 2024, short-duration torrential rains hit Northeastern China. A severe marine heatwave occurred in China’s offshore simultaneously, significantly affecting water vapor transport and precipitation system evolution. From the air-sea interaction perspective, this study analyzes how offshore marine heatwaves regulate atmospheric rivers—weather systems triggering heavy precipitation—to reveal the mechanism by which sea surface temperature anomalies influenced this torrential rain. First, the study identified physical characteristics of atmospheric rivers and marine heatwaves using multi-source meteorological and oceanographic data plus relevant algorithms, and analyzed their correlation with North China’s rainstorm. Then, sea surface temperature sensitivity experiments were conducted via the Weather Research and Forecasting model to diagnose how sea surface temperature anomalies indirectly affect precipitation intensity and distribution through atmospheric rivers. Key conclusions are: (1) Statistical analysis shows atmospheric rivers exist in East Asia in August, with trajectories mostly along the East Asian coast and obvious spatiotemporal variations. On 20 August 2024, a strong atmospheric river extended from South China to Northeast China, moving mainly along China’s eastern coast and providing abundant water vapor for precipitation. (2) Favorable circulation patterns combined with the marine heatwaves jointly drove the formation of atmospheric rivers and precipitation. The extreme precipitation was synergistically driven by an extremely long-persisted marine heatwave over the East China Sea, which provided a continuous moisture source for the atmospheric river. The interaction between upper-level and lower-level jet streams enhanced moisture transport and atmospheric baroclinic instability, thereby promoting the triggering of convective precipitation. (3) Experiments with the WRF+3DPWP show the long-persisted marine heatwave affects lower atmospheric circulation, strengthening the southeasterly jet along China’s eastern coast to boost atmospheric river intensity and related precipitation. Cyclonic circulation anomalies near the Yellow Sea also promote trough and cold vortex formation. Besides, higher sea surface temperature increases low-level atmospheric humidity and water vapor flux, enhances atmospheric instability, and promotes convective system development. From the novel “marine heatwave–atmospheric river–heavy rainfall” perspective, this study clarifies the 2024 summer North China torrential rain’s physical mechanisms and influencing factors, highlights local air-sea interaction’s role in short-term weather and climate, and provides new references for improving heavy rainfall prediction.